Ask Questions, Get Answers

Want to ask us a question? Click here
Browse Questions
0 votes

If $ \cos^{-1}\Large\frac{x}{2}+\normalsize\cos^{-1}\large\frac{y}{3}=\theta ,\;\normalsize prove\;that\;9x^2-12xy\cos\theta +4y^2=36\sin^2\theta $

Can you answer this question?

1 Answer

0 votes
  • \(sin(cos^{-1}x)=\sqrt{1-x^2}=cos(sin^{-1}x)\)
  • \( cos (A+B)=cosa\: cosB-sina\: sin B\)
  • \( cos^{-1}cosx=x=cos\: cos^{-1}x\)
Taking cos on both sides \( cos\theta = cos \bigg[ cos^{-1}\large\frac{x}{2}+cos^{-1}\large\frac{y}{3} \bigg] \)
\( \Rightarrow cos\theta = \large\frac{x}{2}.\large\frac{y}{3}-\sqrt{1-\large\frac{x^2}{4}} \sqrt{1-\large\frac{y^2}{9}}\)
\( cos\theta-\large\frac{xy}{6}=-\large\frac{\sqrt{4-x^2}.{9-y^2}}{6} \)
Squaring both the sides and simplifying which you get the proof.


answered Feb 19, 2013 by thanvigandhi_1
edited Mar 19, 2013 by thanvigandhi_1

Related questions

Ask Question
student study plans
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App